2013
DOI: 10.2196/jmir.2249
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone-Based Intervention With Diaries and Therapist-Feedback to Reduce Catastrophizing and Increase Functioning in Women With Chronic Widespread Pain: Randomized Controlled Trial

Abstract: BackgroundInternet-based interventions using cognitive behavioral approaches can be effective in promoting self-management of chronic pain conditions. Web-based programs delivered via smartphones are increasingly used to support the self-management of various health disorders, but research on smartphone interventions for persons with chronic pain is limited.ObjectiveThe aim of this trial was to study the efficacy of a 4-week smartphone-delivered intervention with written diaries and therapist feedback followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
263
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 144 publications
(273 citation statements)
references
References 54 publications
8
263
0
2
Order By: Relevance
“…Therapist guidance was provided in eight of these studies (Buhrman et al, 2013;Hesser et al, 2012;Kristjánsdóttir et al, 2013;Lappalainen et al, 2014;Lappalainen, Langrial, Oinas-Kukkonen, Tolvanen, & Lappalainen, 2015;Pots et al, 2015;Trompetter, Bohlmeijer, Veehof, & Schreurs, 2015;Weineland, Arvidsson, Kakoulidis, & Dahl, 2012), the duration FIGURE 1 Flow diagram of study selection. Note.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapist guidance was provided in eight of these studies (Buhrman et al, 2013;Hesser et al, 2012;Kristjánsdóttir et al, 2013;Lappalainen et al, 2014;Lappalainen, Langrial, Oinas-Kukkonen, Tolvanen, & Lappalainen, 2015;Pots et al, 2015;Trompetter, Bohlmeijer, Veehof, & Schreurs, 2015;Weineland, Arvidsson, Kakoulidis, & Dahl, 2012), the duration FIGURE 1 Flow diagram of study selection. Note.…”
Section: Interventionsmentioning
confidence: 99%
“…Participants rated the treatments as satisfactory (Trompetter et al, 2015;Lappalainen et al, 2014Lappalainen et al, , 2015, enjoyable (Glick & Orsillo, 2015), useful (Kristjánsdóttir et al, 2013), and helpful (Cukrowicz & Joiner, 2007), as measured by the Client Satisfaction Questionnaire (Attkisson & Zwick, 1982), visual analogue scales, and brief questionnaires, respectively. Four studies administered the Credibility/Expectancy Questionnaire (Borkovec & Nau, 1972;Devilly & Borkovec, 2000) and ratings indicated that participants perceived the third-wave eHealth treatments as credible (Kelly & Carter, 2015;Ljótsson et al, 2010;Ly et al, 2014).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The analyses of the present study are based on data from participants who were randomized to the treatment condition (48 women, see Table 2) in a previously reported RCT [28]. Data consisted of de-identified daily diaries (totaling 3372) and written feedbacks (totaling=799).…”
Section: Samplementioning
confidence: 99%
“…ACT shares important features with CBT, such as behavior activations, although acceptance and cognitive defusion strategies may be relatively unique for ACT [20,22]. Several studies based on ACT have demonstrated effects related to improvement of health outcomes in patients with chronic pain [18,[23][24][25][26], including internetbased interventions [27][28][29]. Studies have also investigated the impact of the different treatment components of ACT [26] as well as mediators of change, supporting the importance of both ACT consistent interventions and changes in processes related to PF [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation